Features of structure of psychophysiological possibilities and physical preparedness of students of different sporting specializations - Kozina Zh.l.; Barybina L.N.; Grin' L.V. (Fizičeskoe Vospitanie Studentov, 2010)
The structure of preparedness of students of different sporting specializations is considered. In research took part 101 students - youths (27 representatives of specialization «football», 19 is a «sambo», 27 is «volley-ball», 28 is «basket-ball»). It is set that for basketball-players and volley-ballers most expressed of individual factor values there is «Speed at run on factors on short and middle distances, jumping», «Cognitiv capabilities (brief memory)», «Propensity to deliberation of actions». For footballers and sportsmen unarmed self-defence factors are most expressed the «Power capabilities», «Concentration of attention», «Psychical stability». Findings can be used for the set of students on different sporting specializations.